The Effect of Friendship Quality towards the Mental Health of Indonesian Migrant Students - Camelia Amanda (CV Projurnal Mitra Publikasi, 2025)
This study aims to explore the influence of friendship quality on the mental health of overseas students through a qualitative approach. Migrant students often face significant emotional and social challenges due to separation from family and friends. Good friendship quality is expected to provide important emotional support in coping with stress and loneliness. This study involved in-depth interviews with 10 overseas students from various universities in Indonesia, who were purposively selected to obtain diverse perspectives. The data obtained was analyzed using thematic analysis to identify patterns and emerging themes related to friendship experiences and their impact on mental health. The results showed that overseas students who have quality friendships tend to feel more connected, have better emotional support, and experience lower levels of anxiety. In addition, factors such as trust, open communication, and common interests are important elements in building friendship quality. This study suggests that overseas students should be active in building positive social relationships and educational institutions should provide programs that support social interaction. The findings are expected to provide insights for students, educators, and policy makers in an effort to improve the mental health of overseas students.